A green porous solid carbon source supports denitrification in low C/N salinity wastewater. Issue 30 (27th March 2017) - Li, Hua; Zhang, Jiasong; Zhou, Ziming; Liu, Qingsong; Dong, Hongbiao; Duan, Yafei; Li, Chunhou
Abstract : A green porous composite, the nitrate removal rate of which could reach 98.8% on the first day of denitrification. Abstract : A green porous composite was prepared using two kinds of natural polysaccharides, konjac glucomannan (KGM) and semen litchi (SL) in aqueous medium under mild conditions. The effect of mass ratios of KGM : SL on structures and denitrification was systematically investigated. The intermolecular hydrogen bonds and other synergistic interactions between KGM and SL gave the composite an amorphous phase and honeycomb network structure with a wide range of macropores. Its high porosity and biocompatibility meant the composite had short acclimation time. Nitrate removal rate could reach up to 98.8% on the first day and denitrification rate could reach up to 320.2 ± 5.82 mg N (L −1 d −1 ). In particular, the KGM : SL = 3 : 3 composite exhibited better mechanical property and much longer lifetime during the denitrification reaction. The porous composite can be used as an economical and effective carbon source for denitrification in low C/N wastewater.